Hepatic Heme Metabolism and Its Control - Bonkowsky, Herbert L. (1979)
This review summarizes heme metabolism and focuses especially upon the control of hepatic heme biosynthesis. Activity of δ-aminolevulinic acid synthetase, the first enzyme of heme biosynthesis, is of primary importance in controlling the overall activity of this biosynthetic pathway. Δ-aminolevulinic acid synthetase is subject to inhibition and repression by heme, and numerous basic and clinical studies support the concept that there exists within hepatocytes a “regulatory” heme pool which controls activity of δ-aminolevulinic acid synthetase. In addition, activity of this enzyme is repressed by feeding, especially by ingestion of carbohydrates (the so-called “glucose effect”). Studies pertaining to the mechanisms underlying this effect are also reviewed. The “glucose effect” appears to be mediated by glucose or perhaps by glucose-6-phosphate or uridine diphosphate glucose, rather than by metabolites further removed from glucose itself. Unlike the situation in E. coli, the “glucose effect” in liver of higher organisms is not mediated by alterations in intracellular concentrations of cyclic AMP. Effects of heavy metals, especially iron, on hepatic heme metabolism are also considered. Iron has been found to inhibit formation and utilization of uroporphyrinogen III and to lead to decreased concentrations of microsomal heme and cytochrome P-450. Administration of large amounts of iron is also associated with an increase in activity of heme oxygenase, a property shared by several other metal ions, most notably cobalt. This effect of iron or cobalt administration is similar to the effect of heme administration in increasing heme oxygenase activity; however, we believe it is unlikely that iron, rather than heme itself, is a physiologic regulator of hepatic heme metabolism, although this hypothesis has lately been proposed.